The Role of Psychiatrists and Muslim Faith Healers in Mental Health Issues - Razali, Zul Azlin; Tahir, M. Faiz (IIUM Medical Journal Malaysia, 2018)
Following the announcement of Traditional and Complementary Medicine Act 2013, Muslim faith healers are slowly gaining grounds to make their practice mainstream. One of the major characteristics of Muslim faith healers is the strong inclination to attribute mental illnesses to Jinn possession (demonic possession). Unlike other traditional healers, Muslim faith healers’ primary mode of treatment is Ruqyah, an incantation or generally considered as ‘Du’a or prayers. This article is a sharing by a psychiatrist who has been actively engaging with faith healers in order to understand the world of faith healing including the attitude and knowledge of both the healers and clients while attempting to educate them on modern psychiatry based on bio-psycho-socio-spiritual paradigm. The methodology: 1) Involvement in symposium, seminar and focused group discussion, either as participant or as speaker. 2) Collaborating with local spiritual leader to conduct workshop on mental illness in mosques. 3) Writing articles in scientific and popular publications with and without faith healers as the collaborators. 4) Appearing in radio advocating and discussing about the dilemma of mental illness issue from the religious perspectives, and 5) Participate in workshop conducted by Muslim faith healers. As a result, several issues come to the author’s attention. The divisions of Muslim faith healers are rather complicated, for example Malay traditional healers or bomoh should not be categorized in the same group as Muslim faith healers. The oft-quoted ‘Islamic Medicine’ is problematic in view that it is laced with elements of local cultural value and practice which are not necessarily authentically Islamic. Since Malays make up the biggest community in Malaysia, one has to differentiate between Islam and Muslim. Majority of Muslims misunderstood the term Ruqyah as a form of healing exclusively done by the Muslim faith healers. In conclusion, psychiatrists should engage more proactively with faith and spiritual healers in order to curb stigmatization and delay in seeking psychiatric care and treatment.